Transport of pathogens through saturated porous rocks with variable flow and salinity - Valentina Prigiobbe; Maria Clementina Caputo; Osvalda De Giglio; Antonella Francesca Savino; Antonietta Celeste Turturro; Debora Colella; Mert Ekiz Cetin; Lorenzo De Carlo; Francesco Bagordo; Tiziana Grassi; Giorgio Cassiani; Mirco Milani; et al. (Journal of Contaminant Hydrology, 2026)

Exploring the fatigue phenomenon in individuals with Parkinson’s disease: an Italian multicenter cross-sectional study - Elisabetta Sarasso; Elisa Pelosin; Ilaria Ruotolo; Manuela Maieron; Alessandro Ferrero; Francesca Quarone; Andrea Grassi; Martina Putzolu; Andrea Gardoni; Giovanna Lagravinese; Francesca Di Biasio; Federica Agosta; et al. (Acta Neurologica Belgica, 2026)
Background Fatigue is a common and disabling non-motor symptom in Parkinson’s disease (PD), significantly affecting patients’ quality of life. However, it is often underdiagnosed due to its subjective nature and the lack of a clear definition, hindering the development of effective treatments. Objectives This study aims to investigate the prevalence of fatigue and its associations with sociodemographic factors, disease severity, levodopa equivalent daily dosage (LEDD) and motor, non-motor, and cognitive symptoms in an Italian cohort of patients with PD. Methods An observational cross-sectional study was carried out in three Italian centers from January to May 2024. One hundred PD patients (H&Y ≤ 4) were assessed using validated tools: Parkinson Fatigue Scale (PFS), Fatigue Severity Scale, and Modified Fatigue Impact Scale. Motor and non-motor signs and symptoms, cognitive status, and LEDD were analyzed using non-parametric tests and Spearman’s correlations. Fatigue prevalence was determined based on PFS score ≥ 3.09. Results Fatigue was present in 36% of patients, more prevalent in women and more severe in those with H&Y > 2. Fatigue correlated strongly with non-motor symptoms (MDS-UPDRS Part I; ρ > 0.6, p p p Conclusions Fatigue in PD is a multidimensional phenomenon influenced mainly by non-motor symptoms. Gender-specific differences and the association with disease progression underscore the need of comprehensive and integrated management strategies to address this challenging symptom.

From cheese whey to single-cell protein production: By-product valorization through acidogenic fermentation and purple phototrophic bacteria - Ali Amini; Andrea Remelli; Valiallah Amirian Mojarad; Mayline El Achkar; Matteo Dell’Anno; Luciana Rossi; Giorgio Mirra; Alessia Di Giancamillo; Francesca Grassi Scalvini; Gabriella Tedeschi; Katia Parati; Andrea Turolla (Bioresource Technology, 2025)

Ensembling satellite monitoring and numerical cartography towards the safety assessment of infrastructures - Francesca Grassi; Paolo Rossi; Benedetta Brunelli; Francesco Mancini; Cristina Castagnetti; Loris Vincenzi; Elisa Bassoli; Alessandro Capra (Applied Geomatics, 2025)
This paper explores new technologies that can advance the state-of-the-practice in safety assessment and health monitoring of existing infrastructures. In this context, multi-temporal interferometric Synthetic Aperture Radar techniques combined with the use of digital models of infrastructures represent a powerful integration to conventional approaches in the monitoring and assessment of structural safety of infrastructures. Although the interferometric method is widely used for ground deformation investigations, using displacement data from satellite observation in structural monitoring is less investigated. The joint use of multi-frequency satellite radar data provided by the European Space Agency Copernicus project and Italian Space Agency will be explored. The paper introduces the workflow implemented for processing satellite radar data from the X-band COSMO-SkyMed constellation by the Italian Space Agency over the municipality of Modena (Italy). An open-source workflow based on Multi-Temporal Interferometric technique and Persistent Scatterers Interferometry is adopted, enabling the detection of displacements of stable targets and the generation of corresponding time series. Radar data products, derived from the processing of both COSMO-SkyMed and Sentinel-1 data, are analyzed in a Geographic Information System alongside the available geospatial dataset of infrastructures. This approach enables the extraction of displacement components related to the ground and infrastructures. The method’s potential for characterizing infrastructures behaviour is assessed through the analysis of selected case studies. The results aim to establish the foundations for a method capable of assessing infrastructure safety.

Assessing landslide susceptibility and dynamics at cultural heritage sites by integrating machine learning techniques and persistent scatterer interferometry - José Eduardo Bonini; Carlotta Parenti; Francesca Grassi; Francesco Mancini; Bianca Carvalho Vieira; Mauro Soldati (Geomorphology, 2025)

A novel pathogenic mutation in the ATP5MC3 gene of ATP synthase causing dystonia is associated with autophagic and lysosomal alteration - Clarissa Gissi; Elisa Zamprogno; Marina Comelli; Francesca D’Este; Federico Caicci; Bruno Grassi; Michela Carraro; Paolo Bernardi; Michael Zech; Giovanna Lippe; Camilla Bean (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Response to microplastic exposure: An exploration into the sea urchin immune cell proteome - Carola Murano; Simona Nonnis; Francesca Grassi Scalvini; Elisa Maffioli; Ilaria Corsi; Gabriella Tedeschi; Anna Palumbo (Environmental Pollution, 2023)

Modeling SARS-CoV-2 spike/ACE2 protein–protein interactions for predicting the binding affinity of new spike variants for ACE2, and novel ACE2 structurally related human protein targets, for COVID-19 handling in the 3PM context - Vincenzo Tragni; Francesca Preziusi; Luna Laera; Angelo Onofrio; Ivan Mercurio; Simona Todisco; Mariateresa Volpicella; Anna De Grassi; Ciro Leonardo Pierri (EPMA Journal, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Effects of 3-month high-intensity interval training vs. moderate endurance training and 4-month follow-up on fat metabolism, cardiorespiratory function and mitochondrial respiration in obese adults - Filippo Vaccari; Angelina Passaro; Andrea D’Amuri; Juana Maria Sanz; Francesca Di Vece; Eleonora Capatti; Benedetta Magnesa; Marina Comelli; Irene Mavelli; Bruno Grassi; Federica Fiori; Giulia Bravo; et al. (European Journal of Applied Physiology, 2020)

The Neuroprotective Role of the GM1 Oligosaccharide, II3Neu5Ac-Gg4, in Neuroblastoma Cells - Elena Chiricozzi; Margherita Maggioni; Erika di Biase; Giulia Lunghi; Maria Fazzari; Nicoletta Loberto; Maffioli Elisa; Francesca Grassi Scalvini; Gabriella Tedeschi; Sandro Sonnino (Molecular Neurobiology, 2019)

Estimation of metabolic syndrome heritability in three large populations including full pedigree and genomic information - Francesca Graziano; Ginevra Biino; Maria Teresa Bonati; Benjamin M. Neale; Ron Do; Maria Pina Concas; Simona Vaccargiu; Mario Pirastu; Oscar Terradura-Vagnarelli; Massimo Cirillo; Martino Laurenzi; Mario Mancini; et al. (Human Genetics, 2019)

Biliverdin Reductase-A Mediates the Beneficial Effects of Intranasal Insulin in Alzheimer Disease - Eugenio Barone; Antonella Tramutola; Francesca Triani; Silvio Calcagnini; Fabio Di Domenico; Cristian Ripoli; Silvana Gaetani; Claudio Grassi; D Allan Butterfield; Tommaso Cassano; Marzia Perluigi (Molecular Neurobiology, 2019)

Combined Used of Rheology and LF-NMR for the Characterization of PVP-Alginates Gels Containing Liposomes - Giulia Fanesi; Michela Abrami; Francesca Zecchin; Irina Giassi; Elena Dal Ferro; Anja Boisen; Gabriele Grassi; Paolo Bertoncin; Mario Grassi; Paolo Marizza (Pharmaceutical Research, 2018)

Environmental quality and hygienic safety of the Alimini Lakes (Puglia, Italy): 20 years of monitoring (1995–2014) - Antonella De Donno; Francesco Bagordo; Francesca Serio; Tiziana Grassi; Gabriele Devoti; Marcello Guido (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Using the DPSIR framework to identify factors influencing the quality of groundwater in Grecìa Salentina (Puglia, Italy) - Francesco Bagordo; Danilo Migoni; Tiziana Grassi; Francesca Serio; Adele Idolo; Marcello Guido; Nicola Zaccarelli; Francesco Paolo Fanizzi; Antonella De Donno (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Rotavirus Occurrence in Shellfish with Low Levels of E. coli - Francesco Bagordo; Tiziana Grassi; Adele Idolo; Francesca Serio; Giovanni Gabutti; Antonella De Donno (Food and Environmental Virology, 2013)

Detection of Viruses in Coastal Seawater Using Mytilus Galloprovincialis as an Accumulation Matrix - Antonella De Donno; Tiziana Grassi; Francesco Bagordo; Adele Idolo; Francesca Serio; Giovanni Gabutti (Food and Environmental Virology, 2012)

Mutant human β4 subunit identified in amyotrophic lateral sclerosis patients impairs nicotinic receptor function - Claudia Moriconi; Silvia Di Angelantonio; Alessio Piccioni; Flavia Trettel; Mario Sabatelli; Francesca Grassi (Pflügers Archiv - European Journal of Physiology, 2011)

Insights into central and peripheral factors affecting the “oxidative performance” of skeletal muscle in aging - Alessandra Ferri; Saverio Adamo; Miriam Longaretti; Mauro Marzorati; Francesca Lanfranconi; Antonietta Marchi; Bruno Grassi (European Journal of Applied Physiology, 2007)

Modulation of fetal and adult acetylcholine receptors by Ca2+ and Mg2+ at developing mouse end-plates - Francesca Grassi; Valentina Degasperi (Pflügers Archiv - European Journal of Physiology, 2000)